JMJD8 overexpression in breast cancer: implications for diagnosis, prognosis, and immune microenvironment interactions - Zhu, Chenlei; Xi, Tianyi; Yang, Guorong; Lu, Wen; Wang, Sentai; Cao, Jiwei (Frontiers in Oncology, 2025)
BackgroundBreast cancer has severe consequences due to late diagnosis and the lack of effective therapies. Currently, potential biomarkers for breast cancer have not been systematically evaluated. Research has shown that JMJD8 is associated with cGAS-STING pathway and plays a role in various tumor microenvironments, but its relationship with breast cancer remains unclear. We investigate the relationship between JMJD8 and the prognosis and immune infiltration microenvironment of breast cancer, exploring its potential as a prognostic biomarker for this type of cancer.MethodsIn this study, we utilized data from The Cancer Genome Atlas (TCGA) to assess the association between JMJD8 expression and clinical characteristics in breast cancer (BRCA) patients through the Wilcoxon signed-rank test and logistic regression. Additionally, we employed Kaplan-Meier and Cox regression methods to confirm the impact of JMJD8 expression levels on overall survival. We constructed JMJD8 knockout BRCA cell lines and studied the effects of JMJD8 protein on tumor cell proliferation and anti-tumor immunity at both cellular and animal levels.ResultsCompared to normal tissues, JMJD8 expression levels were significantly elevated in BRCA tissues. High JMJD8 expression was closely associated with advanced pathological stages and was identified as an independent factor negatively impacting overall survival. In both cellular and animal experiments, JMJD8 knockout relieved the inhibition of the cGAS-STING pathway. This resulted in a significant enhancement of the anti-tumor immune response, as it induced dendritic cell (DC) antigen presentation and maturation, ultimately inhibiting the proliferation of BRCA cells. Furthermore, the JMJD8 expression was positively correlated with the infiltration of M2 macrophages in the tumor microenvironment, suggesting that JMJD8 may contribute to the deterioration of the tumor immunosuppressive microenvironment, potentially leading to reduced patient survival.ConclusionThe elevated expression of JMJD8 in breast cancer tissues is indicative of its involvement in the progression of the disease and its association with immune cell infiltration patterns. Our findings support the hypothesis that JMJD8 could serve as a prognostic biomarker, reflecting the immunosuppressive characteristics of the tumor microenvironment and aiding in the development of targeted therapeutic strategies for breast cancer management.